Digestibility and performance of pacu (Piaractus mesopotamicus) juveniles - fed diets containing different protein, lipid and carbohydrate levels - Abimorad, E. G.; Carneiro, D. J. (Blackwell Publishing, 2007)
Due to lack of information on the use of non-protein energy sources in diets for pacu (Piaractus mesopotamicus), a 2 x 2 x 3 factorial experiment was conducted to evaluate the performance and digestibility of 12 diets containing approximately two crude protein (CP; 220 and 250 g kg(-1)), two lipid (40 and 80 g kg(-1)) and three carbohydrate levels (410, 460 and 500 g kg(-1)). The pacu juveniles-fed diets containing 220 g kg(-1) CP did not respond (P > 0.05) to increased dietary lipid and carbohydrate levels, but the fish-fed diets containing 250 g kg(-1) CP showed a better feed conversion ratio. There were interactions in weight gain (WG), specific growth rate (SGR), crude protein intake (CPI) and feed conversion rate (FCR) dependent on dietary carbohydrate and lipid levels, showing positive effects of increasing carbohydrate levels only for fish-fed diets containing 80 g kg(-1) lipid level. However, when the diets contained 40 g kg(-1) lipid, the best energy productive value (EPV) results were obtained at 460 g kg(-1) carbohydrate. A higher usage of lipids (80 g kg(-1)) reduced CPI and was detrimental to protein [apparent digestibility coefficient (ADC)(CP)] and energy (ADC(GE)), but did not affect growth. The ADC(GE) improved proportionally as dietary carbohydrate levels increased (P < 0.05), increasing the concentration of digestible energy. In addition, the WG, CPI, ADC(GE) results showed best use of the energy from carbohydrates when dietary protein level was 250 g kg(-1) CP. The utilization of 250 g kg(-1) CP in feeds for juvenile pacu for optimal growth is suggested. Therefore, the optimum dietary lipid and carbohydrate levels depend on their combinations. It can be stated that pacu uses carbohydrates as effectively as lipids in the maximization of protein usage, as long as it is not lower than 250 g kg(-1) CP or approximately 230 g kg(-1) digestible protein.
Keywords: carbohydrates; digestibility; growth; lipids; non-protein energy; Piaractus mesopotamicus